Harnessing the Growth Potential of Cloud Computing in Agriculture - Sumit Jaiprakash Rai; Rishabh Ajit Rai (International Journal of Cheminformatics, 2024)
Unlocking the Green Revolution: A Comprehensive Exploration of Cloud Computing Integration in India's Agricultural Landscape. The integration of cloud computing technology in the agricultural sectors of India is poised to play a pivotal role in propelling the nation's holistic development. This paper delves into the dynamic realm of cloud computing, serving as a catalyst for innovation and efficiency in agriculture. By eliminating the need for maintaining expensive computing infrastructure, cloud computing offers a resilient commercial backbone. Operating within a network-centric framework, it promotes the collaborative use of configurable networks, servers, storage, applications, and other essential computing resources. In the contemporary landscape of cloud computing, the centralization of diverse agricultural data, encompassing soil analyses, weather patterns, research outcomes, crop specifics, farmer profiles, marketing statistics, and information on fertilizers and pesticides, proves highly advantageous. This study explores various facets of cloud computing in agriculture, encompassing computing models, distinctive characteristics, deployment models, and cloud service models. Additionally, it investigates the associated benefits and challenges, shedding light on the transformative potential of cloud computing in the agricultural sector.
Keywords: Agriculture; Cloud computing; Community model; Green Revolution; Hybrid model; IaaS; PaaS; Private model; Public model; SaaS